Development of a rapid reverse genetics system for feline coronavirus based on TAR cloning in yeast - Cao, Hongmin; Gu, Haorong; Kang, Hongtao; Jia, Honglin (Frontiers in Microbiology, 2023)
Reverse genetics has become an indispensable tool to gain insight into the pathogenesis of viruses and the development of vaccines. The yeast-based synthetic genomics platform has demonstrated the novel capabilities to genetically reconstruct different viruses. In this study, a transformation-associated recombination (TAR) system in yeast was used to rapidly rescue different strains of feline infectious peritonitis virus, which causes a deadly disease of cats for which there is no effective vaccine. Using this system, the viruses could be rescued rapidly and stably without multiple cloning steps. Considering its speed and ease of manipulation in virus genome assembly, the reverse genetics system developed in this study will facilitate the research of the feline coronaviruses pathogenetic mechanism and the vaccine development.